Vulnerabilidades e estratégias de enfrentamento de mães de filhos com microcefalia - Pimentel, Pollyana Ludmilla Batista (2018)
The increase in the prevalence of infants with congenital microcephaly due to infection with the Zika virus has been a challenge not only for scientists, health workers and government officials, but especially for mothers who have experienced a routine of care, , consultations, stimuli, the majority with exclusive dedication. In this sense, based on the Vulnerability Model and the Strategies of Coping, the general objective of this study was to understand elements of vulnerabilities involved in the care of children with microcephaly and to understand the coping strategies used by these mothers. This was an exploratory, analytical study with a qualitative and quantitative approach, using a sociodemographic questionnaire, interview and the Scale of Modes of Confrontation of Problems (EMEP). Participants were 14 mothers of children diagnosed with microcephaly, with a mean age of 24 years. For the analysis of the quantitative data, descriptive statistics were used with the aid of the SPSS, while the analysis of the interviews was done through the technique of thematic categorical analysis. Most of the interviewees were married or lived in a stable relationship, had a family income of up to two minimum wages and had only one child, and the mean age of children who had microcephaly was 1 year and 1 month, where eight of these children were women. Regarding religion, eight women declared themselves to be Catholic, and on the level of religiousness, eleven mothers claimed to be unreligious or religious. Regarding the analysis of the data obtained from the interviews, with respect to the vulnerabilities, the emergence of three thematic classes (from pregnancy to childbirth, care and care of mothers) was observed. categories and subcategories, showing that the history of these women is surrounded by aspects of vulnerability, both individually, socially and programmatically. According to the data analysis of the Scale of Modes of Confrontation of Problems, the type of coping strategy that obtained the highest average was the Confrontation Focused on the Problem (M = 4.30, SD = 0.52), indicating that before the diagnosis of the child's microcephaly, these mothers go deeper into this problem, in order to obtain more knowledge about, seek the best techniques and treatments for each specificity of their children, aiming at the best prognosis for them. However, the other types of Coping Strategies are also used by the participants of this study, which was corroborated by the analysis of the interviews. It has been found that the myth of maternal love permeates these categories, being present at all times in the lives of these women. The results evidenced the wide complexity experienced by these mothers, an arduous context, imbricated with vulnerabilities, which leads to the search for coping strategies, collaborating with the maintenance of mental health.